Differences in tissue-associated bacteria between metastatic and non-metastatic colorectal cancer - Zhou, Peng; Dai, Ze; Xie, Yaoyao; Li, Tong; Xu, Zhizheng; Huang, Yanhong; Sun, Desen; Zhou, Yuping (Frontiers in Microbiology, 2023)
Background and aims: Accumulated evidence indicates that the intestinal microbiota plays crucial roles in the initiation and progression of CRC. However, the effects of the tissue-associated microbiota on CRC metastasis are poorly defined. The aim of this study was to explore the differences in bacteria between metastatic and nonmetastatic CRC tissues and identify potential bacterial species that associate with CRC metastasis. Methods: 16S rDNA amplicon high-throughput sequencing was used to test the intestinal tissue-associated microbiota in patients with metastatic and nonmetastatic CRC . The microbial diversity and differential species were analysed by standard microbiological methods, and then the differential bacteria were confirmed by qPCR. ROC curves were plotted to evaluate the ability of the differential bacteria in predicting the metastasis of CRC. In addition, the microbial compositions of tumour-adjacent tissues from the metastatic and nonmetastatic CRC groups were analysed. Results: The α-or β-diversity of microbial community between the metastatic and nonmetastatic CRC groups did not exhibit significant differences. However, some bacterial abundances between two groups showed significant differences. At the phylum level, Bacteroidota and Desulfobacterota were significantly higher in the metastatic group than in the nonmetastatic group, while Proteobacteria was significantly decreased in the metastatic group. At the genus level, Bacteroides (mainly composed of Bacteroides fragilis and Bacteroides uniformis) was significantly higher in the metastatic group than in the nonmetastatic group, while Streptococcus and Escherichia-Shigella were significantly decreased. The ROC curves of the selected bacteria showed AUC values ranging from 0.598 to 0.69; when CEA and the selected bacteria were combined, the AUC values increased to 0.678 to 0.705. In addition, the bacterial composition of tumour-adjacent tissues from the metastatic and nonmetastatic CRC groups were also different, and the differential bacteria were consistent with those between metastatic and nonmetastatic CRC tumour tissues. Conclusion: The bacterial composition of tumour and tumour adjacent tissue from the metastatic CRC group was different from that of the nonmetastatic CRC group; in particular, Bacteroides was increased, and Streptococcus was decreased. These findings are helpful to further reveal the mechanism of CRC metastasis and provide new ideas for the clinical diagnosis and treatment of CRC metastasis.